ANALISIS JANUARY EFFECT TERHADAP SAHAM INDEK KOMPAS 100 - Noviarti; Selvi Pratama (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2021)
The purpose of this study is to determine whether there is a January Effect on the Kompas 100 Index. If there is a difference between abnormal returns in January and abnormal returns after January, there will be a January Effect and vice versa. The data used is secondary data. This researcher uses a population of companies listed in the Kompas 100 Index. The method of determining the sample is by using purposive sampling. The observation period is from January to December 2020. This study uses the Mann Whitney U Test to perform a different test. The results of this study indicate that there is a significant difference between the abnormal return value in January and the abnormal return value after January where the results of the study have a significance value of 0.000 <0.05.